2020
DOI: 10.1002/jcb.29656
|View full text |Cite
|
Sign up to set email alerts
|

Screening and verification of microRNA promoter methylation sites in hepatocellular carcinoma

Abstract: The promoter methylation mode of microribonucleic acid (miRNA) plays a crucial role in the process of hepatocellular carcinoma (HCC). Therefore, the primary purpose of this study was to screen and verify the miRNA methylation sites associated with the overall survival (OS) and clinical characteristics of HCC patients. Methylation-related data were from the Cancer Genome Atlas (TCGA). R software was utilized to screen the methylation sites. The least absolute shrinkage and selection operator algorithm was utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Using The Cancer Genome Atlas (TCGA) database, we downloaded BSG expression data related to TC and para-cancerous tissues [23]. Then, the downloaded data were integrated and transferred into the quantile normalized log2 format to improve measurement accuracy.…”
Section: Bsg Mrna Expression In Tc Samples From Tcga Rna-seq Datamentioning
confidence: 99%
“…Using The Cancer Genome Atlas (TCGA) database, we downloaded BSG expression data related to TC and para-cancerous tissues [23]. Then, the downloaded data were integrated and transferred into the quantile normalized log2 format to improve measurement accuracy.…”
Section: Bsg Mrna Expression In Tc Samples From Tcga Rna-seq Datamentioning
confidence: 99%
“…Using The Cancer Genome Atlas (TCGA) database, we downloaded BSG expression data related to TC and para-cancerous tissues [22]. Then, the downloaded data were integrated and transferred into the quantile normalized log2 format to improve measurement accuracy.…”
Section: Bsg Mrna Expression In Tc Samples From Tcga Rna-seq Datamentioning
confidence: 99%
“…MicroRNAs (miRNAs), short 20-22 nucleotides, were recognized to hold essential parts in tumor progression by binding to the 3′untranslated region (3′-UTR) of the target mRNAs [28][29][30][31]. Analysis of miRNA expression has identified a group of dysregulated miRNAs in HCC [32]. According to the bioinformatics results (TargetScan and miRDB) and our previous study showed that ZEB1 may be a target of miR-708.…”
Section: Introductionmentioning
confidence: 99%